Isoflurane vs. Propofol Sedation in Patients with Severe Stroke : A Clinical Proof-of-Concept-Study - Worm, André; Claudi, Christian; Braun, Svea R.; Schenker, Marisa; Meyer, Anneke; Moeller, Leona; Simon, Ole J.; Timmermann, Lars; Mrochen, Anne; Diel, Norma J.; Juenemann, Martin; Huttner, Hagen B.; et al. (My University, 2025)
Background: Severe strokes often require deep sedation, yet the optimal sedation regimen remains unclear. This comparative study compared the efficacy of achieving target sedation depth using inhaled (isoflurane) versus intravenous (propofol) sedation. Methods: This prospective, observational, proof-of-concept study was conducted between July 2022 and June 2023 at two University Hospitals with dedicated neurological intensive care units. We included conservatively treated patients with severe space-occupying strokes (ischemic or haemorrhagic) requiring deep sedation. Patients received either inhaled or intravenous sedation. Sedation targets were defined in the morning rounds using the Richmond-Agitation-Sedation-Scale and were assessed at two subsequent time points (7 p.m. and 7 a.m.) during hospital stay. The primary outcome was the number of days where the predefined sedation target was achieved at both time points, comparing between the two sedation regimens. Secondary and safety outcomes included the incidence of delirium, pneumonia, functional outcomes, mortality, and vasopressor doses. Results: Seventy-nine patients (age 71 [63–81] years, 31 female) were included. Patients sedated with isoflurane achieved the sedation target significantly more often, with 182/444 (41%) compared to 80/497 (16%) assessments in patients sedated with propofol (RR 1.4; 95%-CI: 1.3–1.6). This effect was consistent across all sedation stages, specifically in the deep sedation targets (RR 1.5; 95%-CI: 1.2–1.9) and no-sedation target (RR 5.1; 95%-CI: 2.8–9.4). Secondary and safety outcomes revealed no significant differences. Conclusions: Isoflurane sedation offers a benefit for invasively ventilated stroke patients with respect to sedation targets. Specifically, isoflurane facilitates faster awakening when transitioning from deep sedation to awakening. These data encourage further confirmatory studies for specific stroke-patient groups.
Keywords: ddc:610